1991
DOI: 10.1103/physrevlett.66.923
|View full text |Cite
|
Sign up to set email alerts
|

Transport Anomalies and Internal Structural Models of Stable Quasicrystals

Abstract: Giant transport anomalies in (Fe,Ru)-Cu-Al quasicrystals can be explained by an internal structural model based on two large building blocks, one icosahedral and one layered. The model explains a wide variety of electronic and structural regularities.PACS numbers: 72.15.-v, 61.42.+h The remarkable similarity of the diffraction pattern of a three-dimensional Penrose tiling to those observed for icosahedral quasicrystals at first led to the assumption that the atomic structure corresponds to small-scale simpl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
11
0

Year Published

1993
1993
2004
2004

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(11 citation statements)
references
References 27 publications
0
11
0
Order By: Relevance
“…It may be noted that the M€ ossbauer result itself can not be taken as an evidence for the existence of two nonequivalent Fe sites in the quasicrystalline structure, or in support of any of the two models described above. However, if one assumes that, in accordance with the proposed structural models [20][21][22][23][24][25], iron atoms have two non-equivalent sites, then the analysis of the spectrum in terms of two doublets would yield information about the local order around the two Fe sites. The effect The data was fitted using two different procedures as described in the text.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…It may be noted that the M€ ossbauer result itself can not be taken as an evidence for the existence of two nonequivalent Fe sites in the quasicrystalline structure, or in support of any of the two models described above. However, if one assumes that, in accordance with the proposed structural models [20][21][22][23][24][25], iron atoms have two non-equivalent sites, then the analysis of the spectrum in terms of two doublets would yield information about the local order around the two Fe sites. The effect The data was fitted using two different procedures as described in the text.…”
Section: Methodsmentioning
confidence: 99%
“…In this model, the Fe atoms are expected to occur on two different sites, corresponding to the n and n 0 surfaces in the 6D space. In another, conceptually very different, structural model [24] it has been suggested that the internal structure of Al-Cu-Fe is based upon two large building blocks; the first one is icosahedral, while the second is a layered one, derived from the compound Al 7 Cu 2 Fe. This inhomogeneous or twocomponent quasicrystal model was also supported by a photoelectron spectroscopy study of i-Al 65 Cu 20 F 15 and c-Al 7 Cu 2 Fe [25].…”
Section: Methodsmentioning
confidence: 99%
“…On the theoretical side, except for the structural model of Phillips and Rabe [11], electronic properties have been studied by similarity with Hume-Rothery alloys [12]. In particular the existence of a pseudogap near the Fermi level due to diffraction by Bragg planes seems determined, and has been confirmed by ab initio calculations on approximant phases [13,14].…”
Section: Ebmentioning
confidence: 99%
“…Meanwhile, whether the absence of a real gap is also due to "quasiperiodicity" needs to be investigated. Taking a different viewpoint, an internal structural model (27) advocates that in the ordered i-phases, the icosahedral atomic blocks that are metallic, are enveloped by a layered-structure network that is insulating with an energy gap. This structural arrangement leads to a proximity tunneling type of conductivity with a finite density of states at the Fermi level.…”
mentioning
confidence: 99%